Reviewing the Function Electronic Content in History Learning in university (The First Step in Identifying Critical Electronic Content Requirements) - Hooshang Khosrobeigi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The rapid generalization of educational technology can be seen as a revolution in education. Accordingly, the forthcoming, not too distant, in the "Council for the Study of Texts and Textbooks" seems to be the focus on examining the content of electronic textbooks along with printed books. The initial step in criticizing electronic content is identifying features, functions, and requirements of an electronic syllabus.The purpose of this research is to review the requirements and the production of academic electronic content in the field of history. This is an attempt to get an idea of how these works are appropriately criticized. A part of these studies is about how to use multimedia facilities in electronic content to teach history at the university. Based on this, the main issue of this study is how to align history teaching with the capabilities, methods, and tools of education in the electronic education system and electronic content. This study was conducted using descriptive-analytical method. This study showed that the nature and content of the history courses are very much aligned with e-learning. The data from this research can be a useful tool for developing a critique of electronic content, especially in the field of history.